2004
DOI: 10.1081/drt-120030003
|View full text |Cite
|
Sign up to set email alerts
|

EHD-Enhanced Water Evaporation

Abstract: The enhancement of water evaporation by electrostatic field (corona wind) has been experimentally evaluated in this study. Two sets of experiments were conducted, with and without cross-flow, at an increment of 1 kV from the corona threshold voltage until the occurrence of sparkover. Two types of electrodes (wire and needle) were used. In addition, both positive and negative corona discharges were applied. The weight loss of water due to evaporation as well as the ambient temperature and humidity were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…In addition, the applied electric field also accelerates the solvent evaporation rate as has been reported in the literature. [21] As a result, the polymer chains are quickly frozen and the QDs are confined to their place before they reach their lowest Gibbs free energy. This speculation was confirmed by the following two experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the applied electric field also accelerates the solvent evaporation rate as has been reported in the literature. [21] As a result, the polymer chains are quickly frozen and the QDs are confined to their place before they reach their lowest Gibbs free energy. This speculation was confirmed by the following two experiments.…”
Section: Resultsmentioning
confidence: 99%
“…For a laminar tangential flow over a surface, the combined effect of inertia and electrical force could lead to a fourfold increase of the Nusselt and Sherwood numbers (Sadek et al 1972). Nevertheless, in the specific case of evaporation by a flow over a surface, the enhancement was not observed (Lai and Sharma 2005;Lai et al 2004). Experiments showed that the inertial effects were more predominant than the electrical effects.…”
mentioning
confidence: 83%
“…Thus, production of turbulence by positive corona is more usable. Also, the effect of corona wind for a wire electrode with negative discharge is weaker than that of a wire electrode with positive discharge in the presence of large cross-flow [15]. In this paper, there are cross-flow with the Reynolds number of 8478 and 18,652.…”
Section: Computational Geometrymentioning
confidence: 88%
“…For the current numerical analysis, a 3D computational domain has been considered based on the experimental study reported by Lai et al [15], which consists of a rectangular channel and a Water container which is mounted on the base of the rectangular channel ( Fig. 1).…”
Section: Computational Geometrymentioning
confidence: 99%
See 1 more Smart Citation